1985
DOI: 10.1172/jci111776
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia. A link between hypertension obesity and glucose intolerance.

Abstract: Hypertension and glucose intolerance, determined in a random population sample (n = 2,475), showed a highly significant (P < 0.001) association from the mildest levels of both conditions, independent of the confounding effects of age, sex, obesity, and antihypertensive medications. Summary rate ratios for hypertension were 1.48 (1.18-1.87) in abnormal tolerance and 2.26 (1.69-2.84) in diabetes compared with normal tolerance. Altogether, 83.4% of the hypertensives were either glucoseintolerant or obese-both est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
547
7
23

Year Published

1987
1987
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,392 publications
(606 citation statements)
references
References 65 publications
26
547
7
23
Order By: Relevance
“…This suggested the coexistence of hypertension and glucose intolerance, which has been observed in many other studies. [1][2][3][4][5][6] An independent association of hyperinsulinaemia with hypertension has also been reported in many other studies. 5,[22][23][24][25][26] However, most of the studies have been cross-sectional, and thus the presence of hyperinsulinaemia could be a consequence of hypertension or hyperlipidaemia rather than a cause of these disorders.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This suggested the coexistence of hypertension and glucose intolerance, which has been observed in many other studies. [1][2][3][4][5][6] An independent association of hyperinsulinaemia with hypertension has also been reported in many other studies. 5,[22][23][24][25][26] However, most of the studies have been cross-sectional, and thus the presence of hyperinsulinaemia could be a consequence of hypertension or hyperlipidaemia rather than a cause of these disorders.…”
Section: Discussionsupporting
confidence: 70%
“…This may suggest that hyperinsulinaemia is a link between hypertension and obesity and that the association of hypertension with obesity is mediated by hyperinsulinaemia. 1,5 It is concluded that an elevated fasting insulin concentration as well as an increased BMI preceded the onset of hypertension in subjects with IGT at baseline. It may suggest a causal relationship between hypertension and hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Modan et al 4 suggested that there is a relationship between insulin levels and blood pressure, and several groups have hypothesized that insulin resistance and/or hyperinsulinemia contribute to the pathogenesis of hypertension. 5,6 Thus, insulin has an important role in pathophysiological regulation of the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Insulin resistance with compensatory hyperinsulinaemia has been observed in lean hypertensives, obese normotensives and hypertensives and in patients with type 2 diabetes mellitus. 2,[14][15][16][17][18] Infusions of insulin have been shown to increase blood pressure (BP) in rats. 19,20 In addition to insulin, glucose per se may play a role in hypertension.…”
Section: Introductionmentioning
confidence: 99%